2018
DOI: 10.1073/pnas.1808217115
|View full text |Cite
|
Sign up to set email alerts
|

Akt-mediated platelet apoptosis and its therapeutic implications in immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by low platelet count which can cause fatal hemorrhage. ITP patients with antiplatelet glycoprotein (GP) Ib-IX autoantibodies appear refractory to conventional treatments, and the mechanism remains elusive. Here we show that the platelets undergo apoptosis in ITP patients with anti-GPIbα autoantibodies. Consistent with these findings, the anti-GPIbα monoclonal antibodies AN51 and SZ2 induce platelet apoptosis in vitro. We demonstrate that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 73 publications
6
52
0
Order By: Relevance
“…JC-1 assays measure Ψm depolarisation of the mitochondria membrane, and such depolarisation indicates active cell apoptosis and accelerated ageing. [59][60][61] Beego significantly reduced the percentage of JC-1 green fluorescence ( figure 4H), suggesting an increase mitochondrial in mitochondrial membrane potential and thus a reduction in intrinsic pathway triggered activation of apoptosis. Consistently, flow cytometry analysis of Annexin V levels revealed a detectable beego-induced reduction in the extent of platelet apoptosis ( figure 4I).…”
Section: Supervised Beego Reduces Platelet Counts But Retains Platelementioning
confidence: 94%
“…JC-1 assays measure Ψm depolarisation of the mitochondria membrane, and such depolarisation indicates active cell apoptosis and accelerated ageing. [59][60][61] Beego significantly reduced the percentage of JC-1 green fluorescence ( figure 4H), suggesting an increase mitochondrial in mitochondrial membrane potential and thus a reduction in intrinsic pathway triggered activation of apoptosis. Consistently, flow cytometry analysis of Annexin V levels revealed a detectable beego-induced reduction in the extent of platelet apoptosis ( figure 4I).…”
Section: Supervised Beego Reduces Platelet Counts But Retains Platelementioning
confidence: 94%
“…In summary, we introduce the first description of platelet apoptosis in severe (ICU) COVID-19 patients, suggesting a strong link between platelet apoptosis and thrombosis. These data may indicate platelet apoptosis as a potential target of COVID-19 treatment as has been suggested for ARDS 39 and other platelet disorders 35,40 .…”
Section: Discussionmentioning
confidence: 66%
“…To exclude potential contribution of platelet hyperactive status in our cohort, we assessed the impact of patients’ sera on platelet apoptosis. Recent data showed that autoantibodies from patients with autoimmune thrombocytopenia (ITP) are able to induce platelet apoptosis 35 . The incubation of sera as well as from IgG fractions from severe COVID-19 patients with platelets from healthy donors induced significant changes in apoptosis markers including ΔΨm depolarization, increased cytosolic Ca 2+ concentration, caspase 9 cleavage, and finally PS externalization.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is the active process of cell death regulated by genes through which aging and abnormal cells are cleared. 18 Treatment with HP induced apoptosis in human megakaryocyte Dami cells. Annexin V-FITC/PI double staining was used to label cells treated with HP for 0 h, 3 h, 6 h, and 9 h. Flow cytometry was used to detect apoptotic cells, revealing the apoptosis rate increased significantly at 3 h after HP exposure.…”
Section: Discussionmentioning
confidence: 99%